Self-polishing marine antifouling transparent coating as well as preparation method and application thereof

Through the free radical polymerization of monomers such as acrylate and the combination of metal compounds, a polished marine anti-fouling transparent coating was prepared, which solved the problem of both antifouling and transparency in the prior art, and achieved high transparency and good antifouling effect. .

CN119119820AActive Publication Date: 2024-12-13OCEAN UNIV OF CHINA +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411376001.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-13
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

When existing marine anti-fouling coatings improve their anti-fouling properties, their transparency is reduced, making it difficult to meet the high transparency needs of equipment such as underwater vehicle visual windows and underwater cameras, affecting detection accuracy and signal transmission.

Method used

Free radical polymerization is carried out using acrylate, methacrylate, hydroxyl-containing acrylate and silane acrylate monomers, combining metal compounds and organic acids to form hydroxyl-containing silane acrylate/acrylate metal salt resin, and mix it with crosslinking agent. , a coating with a three-dimensional network structure is prepared from polished marine antifouling transparent coating.

Benefits of technology

While retaining high anti-fouling characteristics, it achieves a transmittance of more than 80% of the 400-800nm ​​band, meeting the needs of various underwater equipment and avoiding the damage to the equipment by mechanical polishing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119820A_ABST
    Figure CN119119820A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of marine coatings, and provides a self-polishing marine antifouling transparent coating as well as a preparation method and application thereof. The preparation method comprises the following steps: carrying out free radical polymerization reaction on a monomer mixture, an initiator, a chain transfer agent and a solvent, such as an acrylate basic monomer, a hydroxyl-containing acrylate monomer and an acrylic acid silane ester monomer, in protective gas to obtain an acrylic acid prepolymer; the acrylic prepolymer, the metal compound, the organic acid and the solvent react to obtain hydroxyl-containing acrylic silane ester / acrylic metal salt resin, and then the hydroxyl-containing acrylic silane ester / acrylic metal salt resin is mixed with the cross-linking agent and the solvent. The hydroxyl-containing acrylic acid silane ester / acrylic acid metal salt resin has a linear structure, forms a self-polishing marine antifouling transparent coating under the action of a cross-linking agent, is cured into a self-polishing marine antifouling transparent coating with a three-dimensional network structure, has the transmittance of more than 80% at the wave band of 400-800nm, and can meet the requirements of various underwater equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of marine coatings, and in particular to a self-polishing marine antifouling transparent coating and a preparation method and application thereof. Background Art

[0002] With the increasing development and utilization of marine resources, the problems of reduced detection accuracy and signal transmission inaccuracy caused by surface contamination of marine detection facilities or equipment are becoming increasingly serious. At present, the preparation of marine antifouling coatings is mainly through the method of adding functional fillers to antifouling resins, but this preparation method will lead to reduced transparency of the coating, which seriously restricts the application of marine antifouling coatings in marine facilities such as underwater vehicle visual windows, detection windows and underwater cameras. Therefore, it is necessary to provide a marine antifouling coating that can meet the high transparency requirements of marine detection equipment such as underwater vehicle visual windows, detection windows, underwater cameras, etc. while retaining high antifouling properties, thereby ensuring the visibility of the window and the accuracy of the detection data. Summary of the invention

[0003] The purpose of the present invention is to provide a self-polishing marine antifouling transparent coating and a preparation method and application thereof in view of the deficiencies in the prior art.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a self-polishing marine antifouling transparent coating, comprising the following steps:

[0006] 1) mixing acrylate base monomers, methacrylate base monomers, hydroxyl-containing acrylate monomers, acrylic acid, methacrylic acid and silane acrylate monomers to obtain a monomer mixture;

[0007] 2) mixing the first part of the monomer mixture, the first part of the initiator, the chain transfer agent and the solvent I in a protective gas to carry out a first free radical polymerization reaction to obtain a first reaction solution;

[0008] 3) mixing the second part of the monomer mixture, the second part of the initiator and the first reaction solution, and performing a second free radical polymerization reaction to obtain a second reaction solution;

[0009] 4) mixing the third part of the initiator and the second reaction solution to carry out a third free radical polymerization reaction to obtain an acrylic acid prepolymer;

[0010] 5) In a protective gas, an acrylic acid prepolymer, a metal compound, an organic acid and a solvent II are mixed and reacted to obtain a hydroxyl-containing silane acrylate / acrylic acid metal salt resin, which is recorded as component A;

[0011] 6) Component A and the crosslinking agent are mixed to obtain a self-polishing marine antifouling transparent coating.

[0012] Preferably, the acrylic acid ester base monomer comprises one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate;

[0013] The methacrylate base monomer comprises one or more of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isooctyl methacrylate, lauryl methacrylate and octadecyl methacrylate;

[0014] The hydroxyl-containing acrylic acid ester monomer comprises one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, N-hydroxymethyl acrylamide and N-hydroxyethyl acrylamide;

[0015] The silane acrylate monomer comprises triisopropylsilyl acrylate and / or triisopropylsilyl methacrylate;

[0016] The initiator comprises one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl perbenzoate, methyl ethyl ketone peroxide, ammonium persulfate and potassium persulfate;

[0017] The chain transfer agent comprises one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, carbon tetrachloride, disulfide ester and iodoform;

[0018] Solvent I and solvent II independently contain one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone and methyl isobutyl ketone;

[0019] The metal compound comprises one or more of zinc oxide, copper oxide, magnesium oxide, calcium oxide, zinc hydroxide, copper hydroxide, iron hydroxide, magnesium hydroxide and calcium hydroxide;

[0020] The organic acid comprises one or more of benzoic acid, cyclohexane acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, abietic acid, proline, leucine, phenylalanine, arginine, dimerized abietic acid, disproportionated abietic acid, salicylic acid, furoic acid and p-chlorobenzoic acid;

[0021] The crosslinking agent comprises one or more of tetraethyl orthosilicate, polyisocyanate and gamma-aminopropyltriethoxysilane.

[0022] Preferably, the molar ratio of the acrylic acid ester base monomer, the methacrylic acid ester base monomer, the hydroxyl-containing acrylic acid ester monomer, the acrylic acid, the methacrylic acid and the acrylic acid silane ester monomer is 20-100: 0-40: 5-50: 10-40: 5-40: 2-10;

[0023] The mass of the first part of the monomer mixture is 10-30% of the total mass of the monomer mixture, the total mass of the first part of the initiator, the second part of the initiator and the third part of the initiator is 0.8-3.2% of the total mass of the monomer mixture, and the mass ratio of the first part of the initiator, the second part of the initiator and the third part of the initiator is 10-30:40-70:15-30;

[0024] The mass ratio of the monomer mixture, the chain transfer agent and the solvent I is 100:0.3-2:75-150.

[0025] Preferably, in step 2), the temperature of the first free radical polymerization reaction is 75-110°C, and the time of the first free radical polymerization reaction is 15-45 min; in step 3), the temperature of the second free radical polymerization reaction is 80-110°C, and the time of the second free radical polymerization reaction is 30-60 min; in step 4), the temperature of the third free radical polymerization reaction is 80-110°C, and the time of the third free radical polymerization reaction is 2.5-3.5 h.

[0026] Preferably, in step 5), the reaction temperature is 75-110° C., and the reaction time is 3-10 h; the protective gas independently comprises nitrogen, argon, helium or neon.

[0027] Preferably, in step 5), the molar ratio of the metal compound to the organic acid is 0.5-1:1, the ratio of the total molar ratio of the metal compound and the organic acid to the total molar ratio of acrylic acid and methacrylic acid is 1-2:1, and the mass ratio of the total mass of the metal compound and the organic acid to the mass ratio of the solvent II is 1:1-2.

[0028] Preferably, step 6) further comprises solvent III, and the mass ratio of component A, cross-linking agent and solvent III is 30:0.5-5:0-10; the solvent III comprises one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone and methyl isobutyl ketone.

[0029] The invention also provides a self-polishing marine antifouling transparent coating prepared by the preparation method.

[0030] The present invention also provides the use of the self-polishing marine antifouling transparent coating in marine detection equipment, wherein the self-polishing marine antifouling transparent coating is coated and then cured.

[0031] Preferably, the coating thickness is 200-800 μm, the curing temperature is 20-30° C., and the curing time is 20-28 hours.

[0032] Beneficial effects of the present invention:

[0033] The invention carries out free radical polymerization reaction on acrylic acid ester base monomers, hydroxyl-containing acrylic acid ester monomers and acrylic acid silane ester monomers, etc., to prepare acrylic acid silane ester / acrylic acid metal salt resin with linear structure and hydroxyl-containing, and forms a self-polishing marine antifouling transparent coating under the action of a cross-linking agent, which is coated on the surface of a substrate and cured to form a self-polishing marine antifouling transparent coating with a three-dimensional network structure, which has good hardness, hydrophobicity and self-polishing performance, and has a transmittance of more than 80% in the 400-800nm ​​band, and can meet the use requirements of various underwater equipment; the self-polishing marine antifouling transparent coating of the invention is used for the protection of underwater equipment, and at the same time, the damage to the equipment by antifouling technologies such as mechanical polishing and wiping is avoided. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The wettability of the coatings prepared in Examples 1 to 2 and Comparative Examples 1 to 4;

[0035] Figure 2 The transmittance of the coatings prepared in Examples 1 to 2 and Comparative Examples 1 to 4 under visible light;

[0036] Figure 3 The transmittance of the coatings prepared in Examples 1 to 2 and Comparative Examples 1 to 4 at different wavelengths;

[0037] Figure 4 The antifouling effects of the coatings prepared in Examples 1 to 2 and Comparative Examples 1 to 4 in seawater. DETAILED DESCRIPTION

[0038] The present invention provides a method for preparing a self-polishing marine antifouling transparent coating, comprising the following steps:

[0039] 1) mixing acrylate base monomers, methacrylate base monomers, hydroxyl-containing acrylate monomers, acrylic acid, methacrylic acid and silane acrylate monomers to obtain a monomer mixture;

[0040] 2) mixing the first part of the monomer mixture, the first part of the initiator, the chain transfer agent and the solvent I in a protective gas to carry out a first free radical polymerization reaction to obtain a first reaction solution;

[0041] 3) mixing the second part of the monomer mixture, the second part of the initiator and the first reaction solution, and performing a second free radical polymerization reaction to obtain a second reaction solution;

[0042] 4) mixing the third part of the initiator and the second reaction solution to carry out a third free radical polymerization reaction to obtain an acrylic acid prepolymer;

[0043] 5) In a protective gas, an acrylic acid prepolymer, a metal compound, an organic acid and a solvent II are mixed and reacted to obtain a hydroxyl-containing silane acrylate / acrylic acid metal salt resin, which is recorded as component A;

[0044] 6) Component A and the crosslinking agent are mixed to obtain a self-polishing marine antifouling transparent coating.

[0045] In the present invention, the acrylic acid ester base monomer preferably comprises one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate;

[0046] The methacrylate base monomer preferably comprises one or more of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isooctyl methacrylate, lauryl methacrylate and octadecyl methacrylate;

[0047] The hydroxyl-containing acrylic acid ester monomer preferably comprises one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, N-hydroxymethyl acrylamide and N-hydroxyethyl acrylamide;

[0048] The silane acrylate monomer preferably comprises triisopropylsilyl acrylate and / or triisopropylsilyl methacrylate;

[0049] The initiator preferably comprises one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl perbenzoate, methyl ethyl ketone peroxide, ammonium persulfate and potassium persulfate;

[0050] The chain transfer agent preferably comprises one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, carbon tetrachloride, dithioester and iodoform;

[0051] Solvent I and solvent II independently preferably comprise one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone and methyl isobutyl ketone;

[0052] The metal compound preferably comprises one or more of zinc oxide, copper oxide, magnesium oxide, calcium oxide, zinc hydroxide, copper hydroxide, iron hydroxide, magnesium hydroxide and calcium hydroxide;

[0053] The organic acid preferably comprises one or more of benzoic acid, cyclohexane acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, abietic acid, proline, leucine, phenylalanine, arginine, dimerized abietic acid, disproportionated abietic acid, salicylic acid, furoic acid and p-chlorobenzoic acid;

[0054] The crosslinking agent preferably comprises one or more of tetraethyl orthosilicate, polyisocyanate and γ-aminopropyltriethoxysilane.

[0055] In the present invention, the molar ratio of the acrylate base monomer, methacrylate base monomer, hydroxyl-containing acrylate monomer, acrylic acid, methacrylic acid and silane acrylic acid monomer is preferably 20-100:0-40:5-50:10-40:5-40:2-10, more preferably 50-90:10-30:10-30:15-30:10-30:2.5-7, and more preferably 85:20:20:25:25:5.

[0056] The mass of the first part of the monomer mixture is preferably 10-30% of the total mass of the monomer mixture, more preferably 15-25%, and more preferably 20%; the total mass of the first part of the initiator, the second part of the initiator, and the third part of the initiator is preferably 0.8-3.2% of the total mass of the monomer mixture, more preferably 1.0-2.5%, and more preferably 2%; the mass ratio of the first part of the initiator, the second part of the initiator, and the third part of the initiator is preferably 10-30:40-70:15-30, more preferably 15-25:50-65:18-25, and more preferably 20:60:20;

[0057] The mass ratio of the monomer mixture, the chain transfer agent and the solvent I is preferably 100:0.3-2:75-150, more preferably 100:0.8-1.5:100-120, and even more preferably 100:1.0:110.

[0058] In the present invention, the temperature of the first free radical polymerization reaction in step 2) is preferably 75-110°C, more preferably 80-100°C, and more preferably 90°C; the time of the first free radical polymerization reaction is preferably 15-45min, more preferably 20-35min, and more preferably 30min; the temperature of the second free radical polymerization reaction in step 3) is preferably 80-110°C, more preferably 90-100°C; the time of the second free radical polymerization reaction is preferably 30-60min, more preferably 40-50min, and more preferably 45min; the temperature of the third free radical polymerization reaction in step 4) is preferably 80-110°C, more preferably 85-100°C; the time of the third free radical polymerization reaction is preferably 2.5-3.5h, and more preferably 3h.

[0059] In the present invention, in step 3), the second part of the monomer mixture and the second part of the initiator are preferably mixed to obtain a mixed solution, and the mixed solution is evenly divided and mixed with the first reaction solution in batches; the even division is preferably 5 to 15 parts, more preferably 10 parts; the batches are preferably separated by an interval of 10 to 20 minutes, more preferably by an interval of 15 minutes; and the second free radical polymerization reaction is preferably started after all the mixed solution is mixed with the first reaction solution.

[0060] In the present invention, in step 4), the third part of the initiator is preferably evenly divided and mixed with the second reaction solution in batches; the evenly divided is preferably 1 to 3 parts, more preferably 2 parts; the batches are preferably separated by an interval of 20 to 40 minutes, more preferably by an interval of 25 to 30 minutes; preferably, the timing of the third free radical polymerization reaction is started after all the third part of the initiator is mixed with the second reaction solution.

[0061] In the present invention, the reaction temperature in step 5) is preferably 75-110°C, more preferably 80-100°C, and more preferably 90°C; the reaction time is preferably 3-10h, more preferably 4-8h, and more preferably 5-7h; the protective gas independently preferably comprises nitrogen, argon, helium or neon.

[0062] In the present invention, the molar ratio of the metal compound and the organic acid in step 5) is preferably 0.5-1:1, more preferably 0.6-0.9:1, and more preferably 0.7-0.8:1; the ratio of the total molar ratio of the metal compound and the organic acid to the total molar ratio of acrylic acid and methacrylic acid is preferably 1-2:1, more preferably 1.2-1.8:1, and more preferably 1.5:1; the ratio of the total mass of the metal compound and the organic acid to the mass of the solvent II is preferably 1:1-2, more preferably 1:1.2-1.8, and more preferably 1:1.5.

[0063] In the present invention, in step 5), the acrylic prepolymer is preferably cooled first, and the cooling temperature is preferably 60-70°C, and more preferably 65°C.

[0064] In the present invention, after the reaction in step 5) is completed, it is preferred to heat up the mixture for dehydration until no distilled water is discharged, and the heating temperature is preferably 100-110°C, more preferably 105-106°C.

[0065] In the present invention, step 6) preferably further comprises solvent III, and the mass ratio of component A, cross-linking agent and solvent III is preferably 30:0.5-5:0-10, more preferably 30:1-4:2-8, and more preferably 30:1.2-3:4-6; the solvent III preferably comprises one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone and methyl isobutyl ketone.

[0066] The invention also provides a self-polishing marine antifouling transparent coating prepared by the preparation method.

[0067] The present invention also provides the use of the self-polishing marine antifouling transparent coating in marine detection equipment, wherein the self-polishing marine antifouling transparent coating is coated and then cured.

[0068] In the present invention, the coating thickness is preferably 200-800 μm, more preferably 300-500 μm, and more preferably 400 μm; the curing temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; the curing time is preferably 20-28h, more preferably 22-26h, and more preferably 24h.

[0069] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0070] Example 1

[0071] In the preparation raw materials of the self-polishing marine antifouling transparent coating, the monomer mixture comprises acrylate basic monomers, acrylic acid, methacrylic acid, N-hydroxymethyl acrylamide and triisopropylsilyl acrylate in a molar ratio of 85:10:10:5:2.5, wherein the acrylate basic monomers comprise n-butyl acrylate, ethyl acrylate and lauryl acrylate in a molar ratio of 50:30:5; the mass of the initiator azobisisobutyronitrile is 1% of the mass of the monomer mixture; the mass of the chain transfer agent n-dodecyl mercaptan is 0.8% of the mass of the monomer mixture; the mass of solvent I (comprising xylene and n-butanol in a mass ratio of 4:1) is equal to the mass of the monomer mixture; the total molar amount of the metal compound zinc oxide and the organic acid benzoic acid is equal to the total molar amount of acrylic acid and methacrylic acid, and the molar ratio of zinc oxide to benzoic acid is 1:1; the mass of solvent II (comprising xylene, n-butanol and butyl acetate in a mass ratio of 4.4:1:10.6) is equal to the total mass of zinc oxide and benzoic acid.

[0072] Under nitrogen protection, 10wt% of the monomer mixture, 15wt% of the initiator, the chain transfer agent and the solvent I were mixed, stirred at a speed of 1000rpm, and reacted at 100°C for 20min to obtain a first reaction solution; the remaining monomer mixture and 65wt% of the initiator were mixed and divided into 10 portions, 1 portion was added to the first reaction solution every 15min, and after 10 portions were added, a timing reaction of 40min was started, and the reaction temperature was controlled at 100°C to obtain a second reaction solution; the remaining initiator was divided into 2 portions, 1 portion was added to the second reaction solution every 30min, and after the addition was completed, a timing reaction of 3h was started, and the reaction temperature was controlled at 85°C to obtain an acrylic prepolymer.

[0073] Under nitrogen protection, the acrylic acid prepolymer is cooled to 70°C, and the cooled acrylic acid prepolymer, metal compound, organic acid and solvent II are mixed and reacted at 90°C for 4 hours; the reaction product is heated to 106°C for dehydration until no distilled water is discharged, thereby obtaining a hydroxyl-containing silane acrylate / acrylic acid metal salt resin, which is recorded as component A.

[0074] Component A and cross-linking agent tetraethyl orthosilicate (TEOS) were mixed in a mass ratio of 30:0.5, and stirred at 2800 rpm for 10 minutes to obtain a self-polishing marine antifouling transparent coating.

[0075] Example 2

[0076] The cross-linking agent in Example 1 was replaced with polyisocyanate (BASF-2100CN), component A, polyisocyanate and xylene were mixed, the mass ratio of component A, cross-linking agent and xylene was 30:1.2:3, the stirring speed of the mixture of component A, cross-linking agent and xylene was changed to 3000 rpm, the stirring time was changed to 15 min, and the rest was the same as Example 1.

[0077] Example 3

[0078] In the preparation raw materials of the self-polishing marine antifouling transparent coating, the monomer mixture comprises acrylate basic monomers, acrylic acid, methacrylic acid, hydroxyethyl acrylate and triisopropylsilyl acrylate in a molar ratio of 85:10:10:10:5, wherein the acrylate basic monomers comprise n-butyl acrylate, ethyl acrylate and lauryl acrylate in a molar ratio of 45:35:10; the mass of the initiator benzoyl peroxide is 3.2% of the mass of the monomer mixture; the mass of the chain transfer agent tert-dodecyl mercaptan is 2% of the mass of the monomer mixture; the mass of solvent I (comprising toluene and ethyl acetate in a mass ratio of 3:1) is 1.5 times the mass of the monomer mixture; the total molar amount of the metal compound copper oxide and the organic acid cyclohexane acid is 1.5 times the total molar amount of acrylic acid and methacrylic acid, and the molar ratio of copper oxide to cyclohexane acid is 0.5:1; the mass of solvent II (comprising toluene, cyclohexanone and butyl acetate in a mass ratio of 3:1:6) is 1.5 times the total mass of copper oxide and cyclohexane acid.

[0079] Under argon protection, 30wt% of the monomer mixture, 25wt% of the initiator, the chain transfer agent and the solvent I were mixed, stirred at a speed of 1000rpm, and reacted at 75°C for 45min to obtain a first reaction solution; the remaining monomer mixture and 50wt% of the initiator were mixed and divided into 10 portions, 1 portion was added to the first reaction solution every 15min, and after 10 portions were added, a timing reaction was started for 60min, and the reaction temperature was controlled at 80°C to obtain a second reaction solution; the remaining initiator was divided into 2 portions, 1 portion was added to the second reaction solution every 25min, and after the addition was completed, a timing reaction was started for 3.5h, and the reaction temperature was controlled at 80°C to obtain an acrylic prepolymer.

[0080] Under argon protection, the acrylic acid prepolymer is cooled to 65°C, the acrylic acid prepolymer, the metal compound, the organic acid and the solvent II are mixed, and reacted at 80°C for 8h; the reaction product is heated to 105°C for dehydration until no distilled water is discharged, and a hydroxyl-containing silane acrylate / acrylic acid metal salt resin is obtained, which is recorded as component A.

[0081] Component A and cross-linking agent γ-aminopropyltriethoxysilane were mixed in a mass ratio of 30:4, and stirred at 3000 rpm for 10 minutes to obtain a self-polishing marine antifouling transparent coating.

[0082] Example 4

[0083] In the preparation raw materials of the self-polishing marine antifouling transparent coating, the monomer mixture comprises acrylate basic monomers, acrylic acid, methacrylic acid, N-hydroxymethyl acrylamide and triisopropylsiloxy acrylate in a molar ratio of 85:10:15:10:5, wherein the acrylate basic monomers comprise n-butyl acrylate, ethyl acrylate and lauryl acrylate in a molar ratio of 40:25:5; the mass of the initiator potassium persulfate is 2% of the mass of the monomer mixture; the mass of the chain transfer agent aliphatic thiol is 1.5% of the mass of the monomer mixture; the mass of solvent I (comprising ethyl acetate and cyclohexanone in a mass ratio of 2:1) is 1.2 times the mass of the monomer mixture; the total molar amount of the metal compound magnesium hydroxide and the organic acid stearic acid is twice the total molar amount of acrylic acid and methacrylic acid, and the molar ratio of magnesium hydroxide to stearic acid is 0.7:1; the mass of solvent II (comprising toluene, ethyl acetate and methyl isobutyl ketone in a mass ratio of 2:1:8) is twice the total mass of magnesium hydroxide and stearic acid.

[0084] Under the protection of helium, 20wt% of the monomer mixture, 20wt% of the initiator, the chain transfer agent and the solvent I were mixed, stirred at a speed of 1000rpm, and reacted at 110°C for 35min to obtain a first reaction solution; the remaining monomer mixture and 60wt% of the initiator were mixed and divided into 10 portions, 1 portion was added to the first reaction solution every 15min, and after 10 portions were added, a timing reaction was started for 30min, and the reaction temperature was controlled at 110°C to obtain a second reaction solution; the remaining initiator was divided into 2 portions, 1 portion was added to the second reaction solution every 30min, and after the addition was completed, a timing reaction was started for 2.5h, and the reaction temperature was controlled at 110°C to obtain an acrylic prepolymer.

[0085] Under the protection of helium, the acrylic acid prepolymer is cooled to 60°C, and the acrylic acid prepolymer, the metal compound, the organic acid and the solvent II are mixed and reacted at 100°C for 10 hours; the reaction product is heated to 110°C for dehydration until no distilled water is discharged, and a hydroxyl-containing silane acrylate / acrylic acid metal salt resin is obtained, which is recorded as component A.

[0086] Component A and cross-linking agent tetraethyl orthosilicate (TEOS) were mixed in a mass ratio of 30:3, and stirred at 2800 rpm for 10 minutes to obtain a self-polishing marine antifouling transparent coating.

[0087] Comparative Example 1

[0088] The cross-linking agent in Example 1 is omitted, component A and xylene are mixed, the mass ratio of component A to xylene is changed to 30:5, the rotation speed of mixing component A and xylene is changed to 2500 rpm, and the rest is the same as Example 1.

[0089] Comparative Example 2

[0090] The crosslinking agent in Example 1 was replaced with γ-glycidyloxypropyltrimethoxysilane (KH560), the mass ratio of component A to the crosslinking agent was changed to 30:1.2, the rotation speed of mixing component A and the crosslinking agent was changed to 3000 rpm, and the rest was the same as Example 1.

[0091] Comparative Example 3

[0092] The crosslinking agent in Example 1 was replaced with methyltriacetoxysilane (METES), the mass ratio of component A to the crosslinking agent was changed to 30:1, the rotation speed of mixing component A and the crosslinking agent was changed to 3000 rpm, and the rest was the same as Example 1.

[0093] Comparative Example 4

[0094] The cross-linking agent in Example 1 was replaced by trimethylolpropane tris[3-(2-methylaziridinyl)propionate (TTMAP), and the mass ratio of component A to the cross-linking agent was changed to 30:0.5. The rest was the same as in Example 1.

[0095] The coatings of Examples 1 to 2 and Comparative Examples 1 to 4 were respectively coated on glass plates (coating thickness was 400 μm), and cured at 25° C. for 24 hours to obtain coatings.

[0096] The wettability of the coatings of Examples 1 to 2 and Comparative Examples 1 to 4 at 25°C was tested using the ContactAngle System OCA contact angle tester of Dataphysics. The results are shown in Figure 1 .Depend on Figure 1 It can be seen that the coating has good hydrophobicity under the action of the cross-linking agent. Since the siloxane structure has the characteristics of low surface energy, the coating with the addition of the cross-linking agent containing the siloxane structure has good hydrophobicity and is not easy to absorb water in an underwater environment, which will not affect the use of optical devices.

[0097] At room temperature, the coatings of Examples 1 to 2 and Comparative Examples 1 to 4 were immersed in seawater in the Yellow Sea of ​​Qingdao, and after being taken out, the coatings were placed on top of the OUC text and placed in a dark box to observe the clarity of the OUC text on the other side of the coating. The transmittance of the coating under visible light conditions was tested after immersion for 3 days and 21 days. The results are shown in FIG. Figure 2 .Depend on Figure 2 It can be seen that the coating with added TTMAP and METES crosslinkers has a lower transmittance under visible light after immersion for 21 days, which is related to the faster hydrolysis rate of the crosslinker in water, resulting in a large number of hydrophilic groups exposed; the coating with added KH560, BASF-2100CN, and TEOS crosslinkers still has a high visible light transmittance after immersion for 21 days.

[0098] The transmittance of the coatings of Examples 1 to 2 and Comparative Examples 1 to 4 at different wavelengths was tested by using a double-beam UV-visible spectrophotometer TU-1901 after being immersed in seawater in the Yellow Sea area of ​​Qingdao for 21 days. The results are shown in Table 1. Figure 3 .Depend on Figure 3 It can be seen that after immersion for 21 days, the coating added with KH560, BASF-2100CN and TEOS crosslinking agent still has a transmittance of not less than 80% at a wavelength of 400-800 nm.

[0099] The coating hardness of Examples 1 to 2 and Comparative Examples 1 to 4 was measured according to GB / T 6739-2022. The results are shown in Table 1.

[0100] Table 1 Coating hardness test results

[0101]

[0102] It can be seen from Table 1 that the hardness of the coating with KH560, BASF-2100CN, TEOS, and TTMAP crosslinking agents added is not less than 4H, has high hardness, and is not easily scratched in a real sea environment.

[0103] The coatings of Examples 1 to 2 and Comparative Examples 1 to 4 were placed 2 meters underwater on a floating antifouling test platform in the Yellow Sea area of ​​Qingdao, from July 19, 2024, to August 19, 2024, to test the inhibitory effect of the coatings on marine fouling organisms. The results are shown in Figure 4 .Depend on Figure 4 It can be seen that the coating surface with the addition of KH560 crosslinker has obvious biological mucosal adhesion and the antifouling effect is reduced; the coating surface with the addition of BASF-2100CN, TEOS, TTMAP, and METES crosslinkers has a good antifouling effect.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a self-polishing marine antifouling transparent coating, characterized in that: The following steps are included: 1) mixing acrylate base monomers, methacrylate base monomers, hydroxyl-containing acrylate monomers, acrylic acid, methacrylic acid and silane acrylate monomers to obtain a monomer mixture; 2) mixing the first part of the monomer mixture, the first part of the initiator, the chain transfer agent and the solvent I in a protective gas to carry out a first free radical polymerization reaction to obtain a first reaction solution; 3) mixing the second part of the monomer mixture, the second part of the initiator and the first reaction solution, and performing a second free radical polymerization reaction to obtain a second reaction solution; 4) mixing the third part of the initiator and the second reaction solution to carry out a third free radical polymerization reaction to obtain an acrylic acid prepolymer; 5) In a protective gas, an acrylic acid prepolymer, a metal compound, an organic acid and a solvent II are mixed and reacted to obtain a hydroxyl-containing silane acrylate / acrylic acid metal salt resin, which is recorded as component A; 6) Component A and the crosslinking agent are mixed to obtain a self-polishing marine antifouling transparent coating.

2. The preparation method according to claim 1, characterized in that: The acrylic acid ester base monomer comprises one or more of methyl acrylate, ethyl acrylate, n-butyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate; The methacrylate base monomer comprises one or more of methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, isooctyl methacrylate, lauryl methacrylate and octadecyl methacrylate; The hydroxyl-containing acrylic acid ester monomer comprises one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, N-hydroxymethyl acrylamide and N-hydroxyethyl acrylamide; The silane acrylate monomer comprises triisopropylsilyl acrylate and / or triisopropylsilyl methacrylate; The initiator comprises one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl perbenzoate, methyl ethyl ketone peroxide, ammonium persulfate and potassium persulfate; The chain transfer agent comprises one or more of n-dodecyl mercaptan, tert-dodecyl mercaptan, carbon tetrachloride, disulfide ester and iodoform; Solvent I and solvent II independently contain one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone and methyl isobutyl ketone; The metal compound comprises one or more of zinc oxide, copper oxide, magnesium oxide, calcium oxide, zinc hydroxide, copper hydroxide, iron hydroxide, magnesium hydroxide and calcium hydroxide; The organic acid comprises one or more of benzoic acid, cyclohexane acid, stearic acid, lauric acid, acetic acid, propionic acid, butyric acid, abietic acid, proline, leucine, phenylalanine, arginine, dimerized abietic acid, disproportionated abietic acid, salicylic acid, furoic acid and p-chlorobenzoic acid; The crosslinking agent comprises one or more of tetraethyl orthosilicate, polyisocyanate and gamma-aminopropyltriethoxysilane.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the acrylic acid ester base monomer, the methacrylic acid ester base monomer, the hydroxyl-containing acrylic acid ester monomer, the acrylic acid, the methacrylic acid and the acrylic acid silane ester monomer is 20-100: 0-40: 5-50: 10-40: 5-40: 2-10; The mass of the first part of the monomer mixture is 10-30% of the total mass of the monomer mixture, the total mass of the first part of the initiator, the second part of the initiator and the third part of the initiator is 0.8-3.2% of the total mass of the monomer mixture, and the mass ratio of the first part of the initiator, the second part of the initiator and the third part of the initiator is 10-30:40-70:15-30; The mass ratio of the monomer mixture, the chain transfer agent and the solvent I is 100:0.3-2:75-150.

4. The preparation method according to claim 3, characterized in that: Step 2) The temperature of the first free radical polymerization reaction is 75-110°C, and the time of the first free radical polymerization reaction is 15-45 minutes; Step 3) The temperature of the second free radical polymerization reaction is 80-110°C, and the time of the second free radical polymerization reaction is 30-60 minutes; Step 4) The temperature of the third free radical polymerization reaction is 80-110°C, and the time of the third free radical polymerization reaction is 2.5-3.5 hours.

5. The preparation method according to claim 4, characterized in that: Step 5) The reaction temperature is 75-110° C., and the reaction time is 3-10 h; the protective gas independently comprises nitrogen, argon, helium or neon.

6. The preparation method according to claim 4 or 5, characterized in that: Step 5) The molar ratio of the metal compound to the organic acid is 0.5-1:1, the total molar ratio of the metal compound and the organic acid to the total molar ratio of acrylic acid and methacrylic acid is 1-2:1, and the total mass ratio of the metal compound and the organic acid to the mass ratio of the solvent II is 1:1-2.

7. The preparation method according to claim 6, characterized in that: Step 6) further comprises solvent III, wherein the mass ratio of component A, crosslinking agent and solvent III is 30:0.5-5:0-10; the solvent III comprises one or more of toluene, xylene, n-butanol, butyl acetate, ethyl acetate, cyclohexanone and methyl isobutyl ketone.

8. A self-polishing marine antifouling transparent coating prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the self-polishing marine antifouling transparent coating according to claim 8 in marine detection equipment, characterized in that: The self-polishing marine antifouling clearcoat is cured after application.

10. The use of the self-polishing marine antifouling transparent coating according to claim 9 in marine detection equipment, characterized in that: The coating thickness is 200-800 μm, the curing temperature is 20-30° C., and the curing time is 20-28 hours.

Citation Information

Patent Citations

  • Rosin organic acid metal salt resin with chemical structural characteristics and performances of acrylate metal salt resin and preparation method and application of rosin organic acid metal salt resin

    CN104530986A

  • Acrylic acid metal salt resin as well as preparation method and application thereof

    CN113087822A

  • Water-based self-polishing marine antifouling paint as well as preparation method and application thereof

    CN118496727A

  • Water-based metal acrylate self-polishing emulsion as well as preparation method and application thereof

    CN118599051A